A Control Model for Reinforced Concrete Work Materials on the Construction of Duta Mall 2 - Daslim, S.; Mursadin, A. (Engineering, Technology & Applied Science Research, 2020)
Controlling is a crucial stage in achieving a project target, covering aspects of cost, quality, and time. In the construction industry, the cost aspect is often the main focus. The project of Duta Mall 2 (DM 2) is the development of an existing building and the cost aspect is a major concern to the owner. Dynamic internal and external factors of the DM 2 project cause the project control to be quite difficult, with the materials becoming the most dominant factor in construction cost. Cost control starts from reinforced concrete work materials, consisting of ready mixed concrete, concrete steel, wire, plywood, timber, and nails. Bad control of material purchasing can lead to cost escalation, degradation of material quality, and impact on the execution schedule of works. This research was conducted to obtain quantitative correlations between material components based on reinforced concrete works material supply data. From these data, some linear regression models can be designed to obtain a more accurate and effective prediction of material volume needs in the future. Model equations can be applied to control material demand, measure waste, reference of material volume in arranging the project cost budget, in addition to the process in the control procedure of the request for goods (materials and equipment).